Small intestinal bacterial overgrowth as an uncommon cause of false positive lactose hydrogen breath test among patients with diarrhea‐predominant irritable bowel syndrome in Asia. Issue 6 (June 2015) - Wang, Yilin; Xiong, Lishou; Gong, Xiaorong; Li, Weimin; Zhang, Xiangsong; Chen, Minhu
Abstract Background and Aim It has been reported that small intestinal bacterial overgrowth (SIBO) may lead to false positive diagnoses of lactose malabsorption (LM) in irritable bowel syndrome patients. The aim of this study was to determine the influence of SIBO on lactose hydrogen breath test (HBT) results in these patients. Methods Diarrhea‐predominant irritable bowel syndrome patients with abnormal lactose HBTs ingested a test meal containing 99mTc and lactose. The location of the test meal and the breath levels of hydrogen were recorded simultaneously by scintigraphic scanning and lactose HBT, respectively. The increase in hydrogen concentration was not considered to be caused by SIBO if ≥ 10% of 99mTc accumulated in the cecal region at the time or before of abnormal lactose HBT. Results LM was present in 84% (31/37) of irritable bowel syndrome patients. Twenty of these patients agreed to measurement of oro‐cecal transit time. Only three patients (15%) with abnormal lactose HBT might have had SIBO. The median oro‐cecal transit time between LM and lactose intolerance patients were 75 min and 45 min, respectively (Z = 2.545, P = 0.011). Conclusions Most of irritable bowel syndrome patients with an abnormal lactose HBT had LM. SIBO had little impact on the interpretation of lactose HBTs. The patients with lactose intolerance had faster small intestinal transit than LM patients.